ANALISIS KESALAHAN PENERJEMAHAN KATA “MUST” PADA CERITA THE MIRROR - Agung Tri Wahyuningsih (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2010)
This article talks about the error analysis on the word “must” translated from English to Bahasa Indonesia. The students tend to use “text” instead of “context” in translating the sentence. It might be caused by their focus on the surface structure (the structure of the sentence) than the deep structure (the message) Therefore studying a new/second/foreign language should not be merely  focused on the sintactical aspect but also semantical aspect.